Oral Vaccine Formulation for Immunocastration Using a Live-Attenuated Salmonella ΔSPI2 Strain as an Antigenic Vector - Sergio A. Bucarey; Lucy D. Maldonado; Francisco Duarte; Alejandro A. Hidalgo; Leonardo Sáenz (Vaccines)
Immunization against Gonadotropin-Releasing Hormone (GnRH) has been successfully explored and developed for the parenteral inoculation of animals, aimed at controlling fertility, reducing male aggressiveness, and preventing boar taint. Although effective, these vaccines may cause adverse reactions at the injection site, including immunosuppression and inflammation, as well as the involvement of laborious and time-consuming procedures. Oral vaccines represent an advancement in antigen delivery technology in the vaccine industry. In this study, a Salmonella enterica serovar Typhimurium (S. Typhimurium) mutant lacking the pathogenicity island 2 (S. Typhimurium ΔSPI2) was used as a vehicle and mucosal adjuvant to deliver two genetic constructs in an attempt to develop an oral immunological preparation against gonadotropin hormone-releasing hormone (GnRH). S. Typhimurium ΔSPI2 was transformed to carry two plasmids containing a modified GnRH gene repeated in tandem (GnRXG/Q), one under eukaryotic expression control (pDNA::GnRXG/Q) and another under prokaryotic expression control (pJexpress::GnRXG/Q). A group of three male BALB/c mice were orally immunized and vaccination-boosted 30 days later. The oral administration of S. Typhimurium ΔSPI2 transformed with both plasmids was effective in producing antibodies against GnRXG/Q, leading to a decrease in serum testosterone levels and testicular tissue atrophy, evidenced by a reduction in the transverse tubular diameter of the seminiferous tubules and a decrease in the number of layers of the seminiferous epithelium in the testes of the inoculated mice. These results suggest that S. Typhimurium ΔSPI2 can be used as a safe and simple system to produce an oral formulation against GnRH and that Salmonella-mediated oral antigen delivery is a novel, yet effective, alternative to induce an immune response against GnRH in a murine model, warranting further research in other animal species.